Pengaruh Risiko Finansial dan Risiko Privasi terhadap Niat Pengadopsian Dompet Digital pada Generasi X di Kota Semarang - Josephine Permatasari Handoyo; Retno Yustini Wahyuningdyah (Universitas Katolik Soegijapranata, Semarang, 2023)
Digital wallet adoption in Generation X is quite low, compare to another productive generations. Gen X is a classified demographic of people which born in the 1965 until 1980 with mature financial level. The research is designed to describe the influence of financial risk and privacy risk to intention to use digital wallet of generation X in Semarang. The samples of this research was 103 respondents who have met the criteria such as live in Semarang and have never used digital wallets. Samples were obtained with purposive sampling-non probability and created with multiple linear regression analysis using SPSS Statistics 21.0. The result showed that financial risk have no partial effect on Generation X’s intention to use digital wallet, while privacy risk have partial effect. Otherwise, financial risk and privacy risk were found to have a simultaneous effect on intention to use digital wallet.